Characterization of isomeric lipid A species from Pseudomonas aeruginosa PAO1 by non-aqueous capillary electrophoresis with positive and negative ion electrospray tandem mass spectrometry - Viktor Sándor; Bettina Űrmös; Ibrahim Aissa; Ágnes Dörnyei; Anikó Kilár (Arabian Journal of Chemistry, 2023)
Pseudomonas aeruginosa is a priority target pathogen for antibiotic research and development because of its high resistance to a wide range of antibiotics. Acquisition of resistance is sometimes associated with modifications of the lipid A component present in the outer membrane of most Gram-negative bacteria. For a deeper understanding of subtle chemical variations of lipid A in relation to biological properties, the structural elucidation of lipid A species within a bacterial strain is of crucial importance. However, the simultaneous presence of monophosphorylated positional isomers in naturally heterogeneous lipid A samples cannot easily be recognized with direct MS measurements or with conventional LC-MS strategies. Herein, we present the application of a non-aqueous capillary electrophoresis (NACE) method coupled to positive and negative ion electrospray tandem mass spectrometry with collision-induced dissociation (CID) activation technique for the in-depth analysis of the lipid A isolate of P. aeruginosa PAO1. The main advantage of our NACE strategy is its separation power regarding the site of phosphorylation of the lipid A structures, which makes it a good orthogonal technique to chromatographic characterizations of the bacterial lipid A composition, where the separation is mainly based on acylation differences of the species. Overall, the results of this electrophoretic approach revealed hitherto unreported isomeric monophosphorylated PAO1 lipid A constituents, including both phosphate and acyl chain positional isomers. The parallel fragmentation in the complementary positive and negative ion modes enabled the unequivocal assignment of the phosphorylation site and position of acyl chains in lipid A compounds of three acylation families ranging from tetra- to hexa-acylation. Moreover, C1-monophosphorylated lipid A species have been identified in P. aeruginosa for the first time.